Identification of novel mutation in cathepsin C gene causing Papillon-Lefèvre Syndrome in Mexican patients - Romero-Quintana José G; Frías-Castro Luis O; Arámbula-Meraz Eliakym; Aguilar-Medina Maribel; Dueñas-Arias Jesús E; Melchor-Soto Jesús D; Romero-Navarro José G; Ramos-Payán Rosalío (BMC, 2013)
Abstract Background Papillon-Lefèvre Syndrome (PLS) is a type IV genodermatosis caused by mutations in cathepsin C (CTSC), with a worldwide prevalence of 1-4 cases per million in the general population. In México, the prevalence of this syndrome is unknown, and there are few case reports. The diagnosis of twenty patients in the state of Sinaloa highlights the need to characterize this syndrome in Mexicans. Methods To understand the basis of PLS in Mexicans, the gene expression, enzymatic activity and mutational analysis of CTSC were assayed in nine PLS patients and their relatives. Frequencies of CTSC gene polymorphisms and HLA alleles were determined in these patients, their relatives, and the population. Results Patients showed normal CTSC gene expression, but a deep reduction (up to 85%) in enzymatic activity in comparison to unrelated healthy individuals. A novel loss-of-function mutation, c.203 T >; G (p.Leu68Arg), was found in all patients, and some carried the polymorphism c.458C >; T (p.Thr153Ile). Allelic frequencies in patients, relatives and controls were 88.89%, 38.24% and 0.25% for G (c.203 T >; G); and 11.11%, 8.82% and 9.00% for T (c.458C >; T). HLA-DRB1*11 was found significantly more frequent (P = 0.0071) in patients than controls (33.33% vs. 7.32%), with an estimated relative risk of 6.33. Conclusions The novel loss-of function mutation of CTSC gene (c.203 T >; G) found in patients correlated with their diminished enzymatic activity, and HLA-DRB1*11 was found to be associated with PLS. The study of more PLS patients may give more insights into the etiology of the disease as well as its prevalence in México.